Determining Interest in the Use of Islamic Financial Products in the Digital Era: The Role of Islamic Financial Literacy, Trust, and Ease of Access - Neni Hardiati Tresna (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Digital transformation has changed the landscape of the financial services industry, including the Islamic finance sector in Indonesia. On the one hand, digital developments open up opportunities to expand access, service efficiency, and market penetration of Islamic financial products. On the other hand, the improvement of digital infrastructure is not automatically followed by the high interest of the public in using Islamic financial products. This article aims to analyze the determinants of interest in using Islamic financial products in the digital era by focusing on three main variables, namely Islamic financial literacy, trust, and ease of access. This study uses a qualitative approach with the type of literature research (narrative literature review). The data sources come from scientific articles, authoritative reports, and policy documents relevant to the theme of adoption of digital Islamic financial services in Indonesia. The results of the study show that Islamic financial literacy functions as a cognitive foundation that helps people understand the principles, products, benefits, and main differentiators of Islamic finance compared to conventional finance. However, literacy alone is not always enough to drive interest in use. Trust appears as a central variable because people tend to use Islamic financial products if they believe in the security of digital services, institutional integrity, sharia compliance, and the ability of institutions to fulfill their service promises. In addition, ease of access—whether in the sense of the ease of opening an account, using the application, reaching out to services, or completing transactions—has a strong influence on the formation of usage intent. This article emphasizes that increasing interest in the use of Islamic financial products in the digital era requires an integrated strategy: strengthening literacy, building institutional trust, and simplifying digital access.